RESULTS OF HIP ARTHROPLASTY AFTER OSTEOSYNTHESIS OF PROXIMAL FEMUR - B. Sh. Minasov; R. R. Yakupov; T. E. Khairov; I. R. Gafarov; K. Kh. Sirodzhov; K. K. Karimov; G. N. Filimonov; A. R. Trubin (Вестник хирургии имени И.И. Грекова)
The hip arthroplasty in case of destructive - dystrophic affection is considered as the most effective method, which provided social and home reintegration. A modern science development facilitates to this technique. However, specialists noted that the rate of endoprosthesis complication increased in the patients after osteosynthesis of proximal femur. The authors compared the results of patient’s treatment that applied hip arthroplasty methods after osteosynthesis of proximal femur. The main group consisted of 38 patients who underwent hip arthroplasty after osteosynthesis of proximal femur. The control group had 43 patients with hip idiopathic osteoarthrosis, who underwent primary arthroplasty. The endoprothesis replacement was associated with increase of the rate of intraoperative and postoperative complications in the main group of patients. According to the results, given group of patients requires a special approach to diagnostics and treatment.